2010
DOI: 10.1246/bcsj.20090326
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Two Vancomycin Complexes with Phosphate and N-Acetyl–d-Ala. Structural Comparison between Low-Affinity and High-Affinity Ligand Complexes of Vancomycin

Abstract: Crystal structures of two vancomycin complexes with phosphate and N-acetyl–d-Ala (AcDA) were determined. Each complex involves two crystallographically independent vancomycin molecules (V1 and V2) in the asymmetric unit, which form a usually observed back-to-back arranged vancomycin dimer V1–V2 with two disaccharide chains packed in a head-to-head manner, but only one of the two ligand-binding sites is occupied. Comparison of the published crystal structures of low-affinity (small in molecular size) ligand com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Aoki et al have reported the crystal structures of complexes formed between Van and peptides terminating with the sequence -d-Ala-d-Lac and have shown that hydrogen bonding interaction between phosphate ions and Van is non-negligible. [22] In neat water, Ac 2 KdAdL is able to replace solvent water found in the antibiotic binding pocket after both desolvation and conformational rearrangement of the binding site have taken place. [23] On the other hand, expulsion of HPO 4 2À and HEPES from the binding pocket is relatively more difficult due to their stronger interactions with Van.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aoki et al have reported the crystal structures of complexes formed between Van and peptides terminating with the sequence -d-Ala-d-Lac and have shown that hydrogen bonding interaction between phosphate ions and Van is non-negligible. [22] In neat water, Ac 2 KdAdL is able to replace solvent water found in the antibiotic binding pocket after both desolvation and conformational rearrangement of the binding site have taken place. [23] On the other hand, expulsion of HPO 4 2À and HEPES from the binding pocket is relatively more difficult due to their stronger interactions with Van.…”
Section: Resultsmentioning
confidence: 99%
“…[23] On the other hand, expulsion of HPO 4 2À and HEPES from the binding pocket is relatively more difficult due to their stronger interactions with Van. Based on recent crystal structure studies, [22,24] a simple model is proposed whereby a water-mediated hydrogen bond interaction between the amide nitrogen of the Lys residue in Ac 2 KdAdL and the oxygen of the terminal carboxylate group of Van is necessary to achieve favorable peptide orientation and energy to remove and replace HPO 4 2À and HEPES from the binding site. This results in a loose Ac 2 KdAdL-Van complex in buffer solution as compared to neat water.…”
Section: Resultsmentioning
confidence: 99%
“…After the cells were washed three times with PBS buffer to remove the unbound Van-porphyrins, the bacterial imaging was conducted upon the excitation of the Q bands of porphyrin under fluorescent microscope. 31 As shown in…”
Section: Bacterial Fluorescent Imaging Of Vancomycin Derivativesmentioning
confidence: 73%
“…With overuse of vancomycin in clinic, in company with that of related glycopeptide antibiotics in animal feeds, vancomycin-resistant Gram-positive bacteria have emerged. 31 The first vancomycin-resistant enterococci (VRE) strain was isolated from patients in an American hospital in 1987. 32 Since then, the prevalence of VRE strains have extended from the local to the global; The percentage of VRE reported among the bacterial infections sharply increased in decades 24,33…”
Section: Occurence Of Vancomycin-resistant Enterococci (Vre) Strainmentioning
confidence: 99%
See 1 more Smart Citation